2010
DOI: 10.1111/j.1462-2920.2010.02253.x
|View full text |Cite
|
Sign up to set email alerts
|

How Pseudomonas aeruginosa adapts to various environments: a metabolomic approach

Abstract: SummaryIn addition to transcriptome and proteome studies, metabolome analysis represents a third complementary approach to identify metabolic pathways and adaptation processes. In order to elucidate basic principles of metabolic versatility of Pseudomonas aeruginosa, we investigated the metabolome profiles of two genetically and morphologically divergent strains, the reference strain PAO1 and the mucoid clinical isolate TBCF10839 in exponential growth and stationary phase in six different carbon sources (cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 51 publications
9
103
0
Order By: Relevance
“…The behavior of P. aeruginosa-and Climax Community-dominated samples matches much of what is recorded in the literature: that the organism grows anaerobically using denitrification in antibiotic-resistant biofilms (Worlitzsch et al, 2002;Palmer et al, 2005;Hogardt and Heesemann, 2010;Schobert and Jahn, 2010). The elevated pH in the media may be due to the production of ammonia from amino-acid breakdown, often observed with P. aeruginosa grown in a CF state (Verhoogt et al, 1992;Barth and Pitt, 1996;Thomas et al, 2000;Frimmersdorf et al, 2010), and previously demonstrated to accumulate in WinCF capillary tubes after the growth of CF microbes . Thus the P. aeruginosa WinCF responses may reflect the true physiology of this microbe and others like it in the CF lung and is in stark contrast to the physiology of the Attack Community during exacerbation events.…”
Section: Sources Of the Fermentative Responsesupporting
confidence: 59%
“…The behavior of P. aeruginosa-and Climax Community-dominated samples matches much of what is recorded in the literature: that the organism grows anaerobically using denitrification in antibiotic-resistant biofilms (Worlitzsch et al, 2002;Palmer et al, 2005;Hogardt and Heesemann, 2010;Schobert and Jahn, 2010). The elevated pH in the media may be due to the production of ammonia from amino-acid breakdown, often observed with P. aeruginosa grown in a CF state (Verhoogt et al, 1992;Barth and Pitt, 1996;Thomas et al, 2000;Frimmersdorf et al, 2010), and previously demonstrated to accumulate in WinCF capillary tubes after the growth of CF microbes . Thus the P. aeruginosa WinCF responses may reflect the true physiology of this microbe and others like it in the CF lung and is in stark contrast to the physiology of the Attack Community during exacerbation events.…”
Section: Sources Of the Fermentative Responsesupporting
confidence: 59%
“…It is widely accepted that P. aeruginosa prefers organic acids and amino acids to glucose in a sequential hierarchy (45,46). Thereby, the catabolism of glucose, via the Entner-Doudoroff pathway, is under the control of the catabolite repression system (44,47). Our cofeed experiments suggest that glucose is a preferred substrate over 2,3-BD for P. aeruginosa.…”
Section: Discussionmentioning
confidence: 65%
“…The carbon source preference of P. aeruginosa and the control of their utilization in nature have been extensively explored (44,45). Here, P. aeruginosa strains PA14 and PAO1 and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…The water-soluble, water-insoluble and solid-state components of seaweed biomass were selected to develop these strategies as an initial step in the chemical profiling of complex biochemical mixtures. The characterization of the water-soluble components via an NMR-based metabolomics approach has been used extensively to study metabolites in a wide range of biological systems in various environments, [6][7][8][9][10][11][12][13] and is capable of creating assignments using our database (that is, SpinAssign program at the PRIMe website). [25][26][27] The water-insoluble …”
Section: Chemical Profiling Of Complex Seaweed Polymers Y Date Et Almentioning
confidence: 99%
“…From this viewpoint, a nuclear magnetic resonance (NMR)-based metabolomics approach is a powerful tool for comprehensively evaluating the metabolic profiles of biochemical complexes in natural ecosystems and has been used extensively to study metabolites from a wide range of biological systems in various environments. [6][7][8][9][10][11][12][13] In addition, an NMR-based metabolomics approach has been applied to biomass profiling for land plant cell wall components. 14,15 However, biomass profiling of water-soluble and water-insoluble (cell wall) components in diverse seaweeds has been largely unexplored in terms of using the comprehensive characterization afforded by an NMR-based metabolomics approach.…”
Section: Introductionmentioning
confidence: 99%